PERKEMBANGAN JUMLAH FRAKSI DPR RI MASA ORDE BARU HINGGA REFORMASI (1966-2004) - Rismauli Simbolon; Yohana Fransisca Br Karo; Timotius Agriva Tarigan; Roberson Dongoran; Roberto Simbolon (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The function of the House of Representatives as stated in the 1945 Constitution of the Republic of Indonesia Article 20A paragraph (1) is a legislative function, a budget function and a supervisory function. The provisions in the 1945 Constitution were then translated into Law Number 22 of 2003 concerning the Structure and Position of the MPR, DPR, DPD and DPRD. The House of Representatives (DPR) in Indonesia has experienced many ups and downs. At least it is divided into 3 (three) periods, namely the Old Order, New Order and Post New Order or Reformation periods. However, in this paper the researcher only discusses the New Order and Post-New Order or Reformation periods. At the beginning of the New Order government, the DPR underwent several changes, both regarding its membership and authority. This research is entitled